"All transport problems are essentially mathematical": The uneven resonance of academic transport and mobility knowledge in Brussels. Issue 3 (16th March 2018) - Kębłowski, Wojciech; Bassens, David
ABSTRACT: This paper presents an inquiry into the capacity of transport and mobility studies to critically engage with contemporary policies. Drawing on the conceptualization of circuits of knowledge, the paper scrutinizes the extent to which transport policy agendas are framed around various approaches within academia. An extensive literature review reveals that the academic field of transport and mobility is organized around a hegemonic core of "neoclassical" and "sustainable" approaches. Meanwhile, a critique of these dominant approaches is emerging in an attempt to (re)embed mobility issues in urban political economy. This threefold knowledge typology visibly resonates within transport policy agendas in Brussels, where we detect a growth-oriented and largely depoliticized dual hegemony of neoclassical and sustainable narratives, with critical academic voices rarely entering official agendas. The paper concludes with a reflection on the difficulties, yet also the need to mobilize critical academic knowledge in the field of transport and mobility.